Regional protest and electoral fraud: evidence from analysis of new data on Russian protest - Lankina, Tomila; Skovoroda, Rodion (Taylor & Francis, 2017)
Does electoral fraud encourage post-electoral protests? To explore the likelihood that citizens would pick up on electoral irregularities perpetrated in their region and engage in post-electoral protest we analyse regional protest event data and voting results for 95,415 precincts in Russia's 2012 presidential elections. We find that regional fraud is associated with post-electoral sub-national protests. Our analysis has important theoretical and policy implications. Protests that not only target specific issues like fraud, but show awareness of where it had been perpetrated can be much more effective than those where blame attribution is vague and generic.